Lesser Black-backed Gulls Larus fuscus thriving on a non-marine diet. Issue 2 (2nd April 2016) - Gyimesi, Abel; Boudewijn, Theo J.; Buijs, Roland-Jan; Shamoun-Baranes, Judy Z.; de Jong, Job W.; Fijn, Ruben C.; van Horssen, Peter W.; Poot, Martin J. M.
ABSTRACT: Capsule : Lesser Black-backed Gulls Larus fuscus breeding 30 km from the coast in the Netherlands focussed entirely on terrestrial food sources and reached relatively high breeding success. Aim : To gain insight in the foraging ecology, habitat use and breeding performance of inland-breeding Lesser Black-backed Gulls. Methods : We received data from seven birds fitted with global positioning system (GPS) loggers. The colony was frequently visited to collect pellets and boluses and to monitor reproductive success, mortality and growth rate of chicks. Results : The GPS data revealed that mainly terrestrial habitats were used, 98% of these GPS positions were within 25 km of the colony. Refuse dumps were the most preferred sites, but also agricultural fields and freshwater bodies were often visited. Only two of the 710 recorded trips were directed to the North Sea. The pellet and bolus analyses confirmed the GPS data: no marine food remains were found. Breeding success of birds in the enclosure was relatively high, with 90% of eggs hatched and 51% of chicks fledged (1.6 chicks/pair). Conclusions : Relying on terrestrial food is feasible when sources are available in the vicinity of the colony. We conclude that Lesser Black-backed Gulls could theoretically shift towards inland breeding after a fishery discards ban.